The effect of colour interpolation on facial skin of virtual humans - Alkawaz, Mohammed Hazim (2013)
The research on facial animation has grown very fast and become more realistic in term of 3D facial data since the laser scan and advance 3D tools can support for creating complex facial model. However, that approaches still lacking in term of facial expression based on emotional condition. Facial skin colour is one parameter that gives an effect to increase the realism of facial expression, since it’s closely related to the emotion which is happens inside the human body. This paper provides a new technique for facial animation to change the colour of facial skin based on trilinear interpolation and bilinear interpolation. The result of colour generation is really comparable to the real human expression; furtherm ore it’s also able to enhance the appearance of facial expression of the virtual human.